Summary of proceedings: Investment consultants and green investment, 3rd stranded assets forum, Waddesdon Manor, 6th March 2015 - Caldecott, B; Rook, D (Smith School of Enterprise and the Environment, 2015)
The University of Oxford's Smith School of Enterprise and the Environment and The Rothschild Foundation held the third Stranded Assets Forum at Waddesdon Manor, Buckinghamshire, on the 6th March 2015. The Forum explored whether the investment consultant industry is up to the job on environmental, climate, and sustainability topics and examined ways to address potential barriers. This report provides a summary of the proceedings and deliberations from the Forum. It outlines the key discussion points and issues that emerged during the sessions held.